Hijacking Sorrow, Joy, Pleasure and Reward: A Philosophical Interpretive Framework for the Theory of Alcohol Addiction - Yevarouski, Valery (Sociologija. Mintis ir veiksmas, 2018)
[full article, abstract in English; only abstract in Lithuanian] This article offers a philosophical interpretation of the key concepts of alcohol addiction in neuroscience (the anhedonia hypothesis, the want-like system, the incentive salience hypothesis) and psychology (the rational choice model). A comprehensive, transdisciplinary review of the theories of alcohol addiction is performed and their applications to the treatment and recovery processes are discussed. As a core component, we reconstruct the experience to become habitual during subsequent alcohol misuse. As a result, the article proposes a philosophical theory for the broad interpretation of the concept of addiction as a reward system disorder with an application for cognitive and behavioral activity.